1993
DOI: 10.1159/000216884
|View full text |Cite
|
Sign up to set email alerts
|

Successful Administration of Low Molecular Weight Heparin in a Patient with Heparin-lnduced Thrombocytopenia and Coumarin-lnduced Skin Necrosis

Abstract: A case of heparin-induced thrombocytopenia and skin necrosis induced by coumarin is reported in a 58-year-old female patient suffering from metastatic breast adenocarcinoma and deep vein thrombosis. The thrombosis resolved after treatment with low molecular weight heparin and the thrombocytopenia recovered within a few days. The occurrence of both these rare complications in the same patient has not been previously reported in the literature. We present a review of these complications and their current treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In addition to the present case, LMW heparin has previously been used successfully for the treatment of venous thrombosis in other patients with warfarin-induced skin necrosis [9,23]. While osteoporosis is a common side effect of chronic administration with standard heparin, recent studies have demonstrated that LMW heparin at therapeutic levels results in less calcium release from bone [24] and less fractures [25].…”
Section: Discussionmentioning
confidence: 65%
“…In addition to the present case, LMW heparin has previously been used successfully for the treatment of venous thrombosis in other patients with warfarin-induced skin necrosis [9,23]. While osteoporosis is a common side effect of chronic administration with standard heparin, recent studies have demonstrated that LMW heparin at therapeutic levels results in less calcium release from bone [24] and less fractures [25].…”
Section: Discussionmentioning
confidence: 65%
“…The treatment of HIT includes discontinuation of heparin and institution of alternative antithrombotic therapy. It has recently been shown that LMW heparin may be beneficial in some patients with HIT [15]. However, the patient described here did not benefit from such therapy, and Enoxaparin was discontinued due to sustained severe thrombocytopenia.…”
Section: Discussionmentioning
confidence: 75%
“…Only a few reports have described a possible association between WISN and HIT [22][23][24][25][26]. However, most of these reports [22][23][24][25] either did not perform diagnostic laboratory testing for HIT antibodies, or described patients who had other underlying disorders, such as adenocarcinoma [27] or congenital protein C deficiency [5][6][7], that are known to predispose to warfarin-induced prothrombotic complications. There have also appeared reports of apparent WISN, in which unexplained thrombocytopenia that began during heparin therapy was noted by the authors [6,28,29].…”
Section: Discussionmentioning
confidence: 99%